RANCANG BANGUN LEARNING MANAGEMENT SYSTEM, STUDI KASUS: SMK WIPAMA CIKUPA - Agus Prianto; Septanto, Henri (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2023)
This study aims to design and develop an effective and efficient learning media at Wipama Cikupa Vocational School, because this Vocational School faces obstacles in terms of limited classroom space and learning time which is divided into two shifts. To overcome this problem, the development of an LMS (Learning Management System) was implemented as a solution to provide learning without distance, place and time limitations. E-learning was chosen as the main approach in this research, because of its flexibility, self-learning ability, and cost efficiency for both administrators and students. The development of this LMS includes the stages of system requirements analysis, user interface design, database design, coding using the PHP programming language, and testing. The development method used is the Waterfall model to ensure planned and systematic development. The testing phase is carried out using a black box approach to ensure compatibility between the system being developed and the desired requirements. The result of this research is the implementation of the LMS (Learning Management System) which allows online learning through a website platform, so that this school can overcome the limitations of classrooms and time, and increase the effectiveness and efficiency of the learning process in this school.